Answer:
x = 3, y = 1 is the solution of the given system.
Step-by-step explanation:
Here, the given system of equations is:
y = -x + 4 ...... (1)
y = x - 2 .......... (2)
Now, to find the solution of the system, SUBSTITUTE the value of y from equation (1) in to the equation (2). We get ,
y = x - 2 ⇒ -x + 4 = x - 2 ( as from (1), y = -x + 4)
or, -x -x = -2 -4
or, - 2 x = -6 ⇒ x = 6/2 = 3
or, x = 3
⇒ y = x - 2 = 3 - 2 = 1
⇒ y = 1
Hence, x = 3, y = 1 is the solution of the given system.
Answer:
1. y = 4
2. x = 10
3. n = 6
4. m = 4
5. h = 2
Step-by-step explanation:
Hope this helps!!
Answer:
4
kind of confusing question
Answer: b) two sides and the included angle are congruent
<u>Step-by-step explanation:</u>
RS = QS SIDES are congruent
∠PSR ≡ ∠PSQ ANGLES are congruent
PS = PS SIDES are congruent
ΔPSR ≡ ΔPSQ by the Side-Angle-Side (SAS) Congruency Theorem
Since we know the triangles are congruent, we can state that their parts are congruent:
Congruent-Parts of-Congruent-Triangles are-Congruent (CPCTC)